Workload even affects hand hygiene in a highly trained and well-staffed setting: a prospective 365/7/24 observational study. Issue 1 (September 2017) - Scheithauer, S.; Batzer, B.; Dangel, M.; Passweg, J.; Widmer, A.
Summary: Introduction: Compliance with hand hygiene (HH) has often not proved satisfactory; high workload is a commonly self-reported reason. Previous studies comparing workload and compliance have not measured workload precisely and have focused on certain times of day. This study aimed to investigate the association between HH compliance and workload, both electronically defined 365/7/24 (primary endpoint). In addition, the quality of commonly used compliance defining methods (hand disinfectant usage, direct observation) was investigated (secondary endpoint). Materials and methods: Correlation of electronically measured HH compliance (hand-rub activities (HRA)/HH opportunities) with electronically determined workload (nursing time output/nursing time input) was undertaken over one year at a stem cell transplant unit at University Hospital Basel, Switzerland. HRA and procedures requiring HRA according to the five World Health Organization indications were recorded continuously (365/7/24) using electronic dispensers and electronic documentation, and compliance was calculated accordingly. Hand disinfectant usage was calculated using spending records for one year; direct observation was performed for approximately 1800 HH opportunities. Results: During the investigation, 208, 184 HRA, translating into 57 [standard deviation (SD) 10] HRA/patient-day (PD), were performed. Electronically determined compliance ranged from 24% to 66% [mean 42.39% (SD 8%)]. The higher the workload, the lower the compliance ( R =-0.411; P <0.001). HRA/PD ( r =-0.037), hand disinfectant usage (mean 160 mL/PD) and observed compliance (95%; 1734 HRA/1813 HH opportunities) were not found to be associated with workload. Conclusion: Calculated compliance was inversely associated with nurses' workload. HRA/PD, observer-determined compliance and amount of disinfectant dispensed were used as surrogates for compliance, but did not correlate with actual compliance and thus should be used with caution.